2010
DOI: 10.1124/jpet.110.176883
|View full text |Cite
|
Sign up to set email alerts
|

BeKm-1, a Peptide Inhibitor of Human ether-a-go-go-Related Gene Potassium Currents, Prolongs QTc Intervals in Isolated Rabbit Heart

Abstract: Drug-induced cardiac arrhythmia, specifically Torsades de pointes, is associated with QT/QTc interval prolongation, thus prolongation of the QT interval is considered as a biomarker for Torsades de pointes risk (N Engl J Med 350:1013-1022, 2004). Specific inhibition of human ether-a-go-go-related gene (hERG) potassium channels has been recognized as the main mechanism for QT prolongation (Cardiovasc Res 58:32-45, 2003). This mechanism has been demonstrated for a variety of smallmolecule agents, which access th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 38 publications
1
13
1
Order By: Relevance
“…The effects of a mid-dose application of BeKm-1 on spontaneously beating hiPS-CMs consistently included cellular repolarization delay, negative chronotropic effects on APs, CaT, and monolayer contractions, which were accompanied with the higher rhythm variability of these parameters. This is in agreement with other studies investigating the effects of BeKm-1 on more integrated models [ 8 ]. Of note, negative chronotropic response is also in accordance with studies with common hERG blockers E4031 and dofetilide on hiPS-CMs [ 13 ] and on rabbit isolated hearts [ 14 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The effects of a mid-dose application of BeKm-1 on spontaneously beating hiPS-CMs consistently included cellular repolarization delay, negative chronotropic effects on APs, CaT, and monolayer contractions, which were accompanied with the higher rhythm variability of these parameters. This is in agreement with other studies investigating the effects of BeKm-1 on more integrated models [ 8 ]. Of note, negative chronotropic response is also in accordance with studies with common hERG blockers E4031 and dofetilide on hiPS-CMs [ 13 ] and on rabbit isolated hearts [ 14 ].…”
Section: Discussionsupporting
confidence: 93%
“…This reported value can be compared to some of the best hERG inhibitors: E4031 (IC 50 = 7.7 nM [ 5 ]), dofetilide (IC 50 = 12 nM [ 6 ]), and astemizole (IC 50 = 26 nM [ 7 ]). The proarrhythmic effect of BeKm-1 was evidenced in rabbit heart, a species expressing ERG channel, where it prolongs the QT interval in the electrocardiogram (ECG) [ 8 ]. Yet, the effect of BeKm-1 has never been tested on hiPS-CMs.…”
Section: Introductionmentioning
confidence: 99%
“… 2006 ), and it has demonstrated sensitivity to detect QT prolongation induced by BeKm-1, a specific peptide inhibitor of the hERG channel (Qu et al. 2011 ). Therefore, this isolated whole heart model can detect QTc prolongation caused by small or large molecules inhibitors that directly interfere with cardiac repolarization.…”
Section: Introductionmentioning
confidence: 99%
“…These models highlight the importance of Triangulation, Reverse use-dependence, Instability (of repolarization current), and Dispersion of Refractoriness, together known as the TRIaD model (2). Haraguchi et al who modeled transmural dispersion of repolarization (TDR) during ventricular tachycardia provide a good example of applying this approach to TdP (24 16). They found that arrhythmia risk in TdP is related to scroll wave stability, and is not directly associated with QT interval width.…”
Section: Relating Risk Factors To Pharmacologic Mechanismsmentioning
confidence: 99%